Predictors of decreased stool frequency in constipated elderly: a hierarchical linear regression model approach - Zulkifli, Khairil Khuzaini; Hassim, Siti Rubiaehtul; Wong, Mung Seong; Abd Samat, Nor Aslina; Abdul Wahab, Patimah; Thevaraajan, Jayaraman; Lee, Yeong Yeh; Mohd Yusoff, Dariah (Gut & Liver, 2019)
Background/Aims Based on our earlier study among the elderly in primary care, The prevalence of functional constipation was 13.5% and 20% reported stool frequency <3 per week. In the current study, we aimed to determine predictors of decreased stool frequency among constipated elderly using a hierarchical linear regression model approach. Methods Consecutive elderly (above 65 years old) participants were recruited after informed consent. In addition to questionnaires (Rome III Questionnaire, demographic, diet and physical activity), patients underwent anorectal studies including high resolution anorectal manometry (M-Compass, Medspira), balloon expulsion test, and colonic transit study (Sitzmarks). Using multiple linear regression, association between a lower stool frequency in constipated elderly and independent factors (three hierarchical models i.e., model 1 demographic, model 2 risk factors and model 3 anorectal parameters) was determined with p<0.05 as significant. Results Of 71 elderly screened, 31 (2/3 females) were recruited, 17 had constipation and 14 without. With univariable analysis, those with versus without constipation reported lower stool frequency, longer duration of defecation, more Bristol type 1, 2 & 3 stools, water intake <6 glass per day, and less income per month (all p<0.05) (Table 1). With hierarchical model analysis, significant predictors of less frequent stools in elderly were the use of medications (adjusted B, –3.41; 95% confidence interval [CI], –6.61 to –0.22; p=0.037) in model 1, Bristol type 1, 2 & 3 stools (adjusted B, –5.4; 95% CI, –8.59 to –2.22; p=0.002) and longer duration of defecation (adjusted B –2.82; 95% CI, –5.34 to –0.31) in model 2, and lastly hyposensitivity (adjusted B, 0.19; 95% CI, 0.06 to 0.31) in model 3. Conclusions Among constipated elderly, the use of medications, Bristol type 1, 2 & 3 stools, longer duration of defecation and hyposensitivity predict less frequent stools.